Enhancement of air-side heat transfer performance of additively-manufactured air-cooled heat exchangers - Chen, Zhenfu (Nanyang Technological University, 2023)
This paper describes the thermo-hydraulic efficacy of a porous lattice heat exchanger which constitutes of varying outer diameters and orientations of Schwarz Primitive surface (P surface) that was designed in Solidworks and its thermo-hydraulic properties were numerically explored in Ansys Fluent simulation. In an earlier section of this study, an experiment was conducted to evaluate and validate the simulated performance of the primary porous lattice heat exchanger. A primary porous lattice heat exchanger has proven to be superior to a conventional heat exchanger based on experimental results achieved. Later in this study, the primary design was leveraged to improve thermo-hydraulic performance during the development of the secondary design, specifically heat transfer coefficient and pressure drop per unit depth.